TERAPAN POLA RITMIK TABUHAN GENDANG REBANA DALAM BENTUK FORMAT STRING QUARTET - Amal, Mukhlisul; Ismunandar, Ismunandar; Indrapraja, Diecky (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTamadun is an Arabic word means build cities. In this case, Tamadun for String Quartet build Melayu music with something new is the presentation form, that is String Quartet which actually unsusual in Melayu traditional music. Through the difference, become an idea to create the Tamadun for String Quartet using western melodic instrument. Violin, Viola and Cello are western instrument that support the idea of Tamadun for String Quartet.Tamadun for Sting Quartet is musical performance that need a production team to reach the goals. This piece is made as afinal examination and also to perfomed for general society. Tamadun for String Quartet applied a method and creation step. This creation step in important to make all of the aspect that will be create in this piece is working systematically and matched with the concept that the composer used in this piece are: observation, exploration, improvitation, and evaluastion. String Quartet is a music form that played as an ensamble with four string players. Generally, Sting Quartet usually play some music piece of Mozart, Beethoven, Vivaldi, and another classical composer. This Tamadun fo String Quartet is a modifications of String Quartet form with Melayu music atmosphere.Â Keywords:Tamadun for String Quartet, Method and Creation Step